Comparative and comprehensive analysis on bacterial communities of two full-scale wastewater treatment plants by second and third-generation sequencing. (September 2020) - Ji, Bin; Wang, Shulian; Guo, Dabin; Pang, Heliang
Abstract: This study investigated the bacterial communities of two typical full-scale WWTPs (anaerobic-anoxic-oxic and Carrousel oxidation ditch processes) by simultaneous Illumina MiSeq sequencing and PacBio sequencing. Both of the two sequencing results revealed that Proteobacteria and Bacteroidetes comprised over 50% of both of the two WWTPs at phylum level. PacBio and MiSeq sequencing could identify about 68% and 50% of the total sequences at genus level, respectively. Bacteria for potential nitrogen removal shared by the two WWTPs included Pseudomonas yamanorum, Nitrospira sp. ND1 and Rhodobacter sp. WS22. However, Comamonadaceae seemed to be the main contributor to phosphorus removal. Specifically, the nitrogen and phosphorus removal-related bacteria accounted for more than 8.2% and approximate 3.8% of the total bacteria for both of the two WWTPs, respectively. Results obtained from this study contribute to the comprehensive understanding of detailed bacteria in full-scale WWTPs. Highlights: Simultaneous MiSeq sequencing and PacBio sequencing were applied. The identified bacterial communities differed at a finer scale by these two methods. More sequences can be classified at genus/species levels by PacBio sequencing. PacBio sequencing is complementary to Miseq sequencing. Still over 50% of the mysterious microorganisms were not identified at species level.